Fe(III)/Bentonite as a Heterogeneous Catalyst for the Synthesis of 3, 4‐dihydropyrimidin‐2‐(1H)‐ones. Issue 44 (27th November 2020) - Chopda, Lakha V; Dave, Pragnesh N.
Abstract: Fe(III) immobilized over natural bentonite (bent) using the impregnation method. Prepared catalysts were well characterized by XRD, FT‐IR and FeSEM. The catalytic activity of three catalysts 10, 20 and 30 % Fe(III)/bent evaluated for the synthesis of 3, 4‐dihydropyrimidin‐2(1H)‐ones known as Biginelli reaction. The catalyst 30 % Fe(III)/bent exhibited a high yield of the product towards the synthesis of a variety of dihydropyrimidones (DHPMs). The high yield of dihydropyrimidone (DHPM) was obtained in model reaction in ethanol, acetonitrile, DMF and solvent ‐ free condition. The reusability test indicated that 6 % of yield of product decreased after 5 th cycle. Abstract : 10, 20 and 30 % Fe(III) was supported over natural bentonite as a heterogeneous catalyst for Biginelli reaction. The 30 % Fe(III) showed highest yield of product and extended for the synthesis of variety of Biginelli adducts produced in good to high yield.